Ananalysis of Branding Strategies for Developing Creative Economy Based on the Regional Potential Resources (A Study in Bau-Bau City, Southeast Sulawesi) - Supriyadi, Supriyadi; Almana, La Ode; Hasnita, Nita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to find out the regional advantage potential empirically and analyze branding strategies in order to encourage the acceleration of regional development that had the potential as a regional growth center, reduce development gaps between regions, and encourage regional growth, especially in Baubau City. This needed to be done as an effort to develop fast-growing strategic areas in the development of creative cities in the region. The key variable in this study was ecosystem-based creative economy branding, namely human resources, goods/services, markets, research, and development. The sampling method used was purposive sampling and snowball sampling. In this study, the concept of a creative economy branding strategy based on superior local resources was arranged using a ranking analysis of the creative economy sub-sector of Bau-Bau City.